Phytochemical Screening, Total Phenolic Content and Antioxidant Activity of Tropical Brown Macroalgae Padina pavonica Hauck from Kabung Island, West Kalimantan - Mega Sari Juane Sofiana; Ikha Safitri; Shifa Helena; Warsidah Warsidah (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
Marine macroalgae are potential sources as carbohydrate alternative, food additive, and bioactive compounds with antioxidant activity. The biological activity is strongly influenced by the type and phenolic compounds concentration. Tropical brown algae Padina pavonica Hauck was found with a large abundance in Kabung Island, West Kalimantan. The objective of this study was to determine the phytochemical screening, total phenolic content, and antioxidant activity of P. pavonica Hauck extract. The phytochemical screening and determination of total phenolic compounds were carried out using two different solvents with ethanol and ethyl acetate. Whereas antioxidant activity was evaluated using the DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenger method with UV-vis spectrophotometer. The qualitative analysis of phytochemical constituents revealed the presence of alkaloids, steroids, flavonoids, phenols, and saponins. Furthermore, for total phenolic compounds, the ethanolic extract had a higher content (20.34 mgGAE/g) dry sample than ethyl acetate extract (7 mgGAE/g). The ethanolic extract also had a higher of potential antioxidant activity which IC50 was 144.47 ppm compared to ethyl acetate extract (IC50 was 191.98 ppm).